GREEN ACCOUNTING: IMPLEMENTATION IN INDONESIA, INDIA DAN YORDANIA - Husda, Anggun Permata; Haldy, Muhammad; Saputra, Asron (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
Understanding the actual environmental impact of businesses and assisting in the implementation of corrective measures to enhance societal value are two major advantages that green accounting offers to the idea of economic welfare. A comparative study is used as the research approach to compare how green accounting is being implemented in India, Jordan, and Indonesia. Comparative results of the adoption of green accounting in Indonesia India & Jordan were obtained through data analysis conducted through a literature study. These results indicate that the three countries are at varying stages of progress. For example, (1) India: More advanced in the implementation of green accounting, with many large companies adopting this practice and strong government support. (2) Indonesia: Still in the early stages of development, with a number of big businesses implementing green accounting and government regulations in place. (3) Jordan: The application of green accounting is still in its infancy, and numerous obstacles need to be addressed.